The Figure of Knowledge : Conditioning Architectural Theory, 1960s - 1990s - Heynen, Hilde; Heynickx, Rajesh, 1977-; Loosen, Sebastiaan (Book collections on Project MUSE., 2020)
It is a major challenge to write the history of post-WWII architectural theory without boiling it down to a few defining paradigms. An impressive anthologising effort during the 1990s charted architectural theory mostly via the various theoretical frameworks employed, such as critical theory, critical regionalism, deconstructivism, and pragmatism. Yet the intellectual contours of what constitutes architectural theory have been constantly in flux. It is therefore paramount to ask what kind of knowledge has become important in the recent history of architectural theory and how the resulting figure of knowledge sets the conditions for the actual arguments made. The contributions in this volume focus on institutional, geographical, rhetorical, and other conditioning factors. They thus screen the unspoken rules of engagement that postwar architectural theory ascribed to.